Meeting key synthetic challenges in amanitin synthesis with a new cytotoxic analog: 5′-hydroxy-6′-deoxy-amanitin. Issue 43 (15th October 2020) - Pryyma, Alla; Matinkhoo, Kaveh; Wong, Antonio A. W. L.; Perrin, David M.
Abstract : Elucidating a highly diastereoselective sulfoxidation of S -deoxy-amanitin to afford α-amanitin and a more synthetically accessible analog of near-native toxicity. Abstract : Appreciating the need to access synthetic analogs of amanitin, here we report the synthesis of 5′-hydroxy-6′-deoxy-amanitin, a novel, rationally-designed bioactive analog and constitutional isomer of α-amanitin, that is anticipated to be used as a payload for antibody drug conjugates. In completing this synthesis, we meet the challenge of diastereoselective sulfoxidation by presenting two high-yielding and diastereoselective sulfoxidation approaches to afford the more toxic ( R )-sulfoxide.